METODE SEMIOTIC VYGOTSKIAN DALAM PEMBELAJARAN MATEMATIKA - Dewi Sukriyah (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2023)
Learning mathematics is one of the social phenomena that occurs in class, so that the interactions that occur between teachers and students are the main focus in mathematics research. The Vygotskian Semiotic Method divides the class into small groups in the learning process. The teacher as a public figure in the class who is an example, mediates discussions in the learning process. Phenomenon studies are analyzed based on the resulting learning videos. The study was conducted interpretatively based on the two methods developed, namely semiotic nodes and semiotic bundles. Semiotic nodes with synchronic tools to focus on how students give meaning to students' actions in understanding mathematical relationships and structures. Semiotic bundle with diachronic tools for signs or key moments of the student's objectification process in pattern generalization activities.